Toxidade aguda e potencial anestésico do hidrolato de Myrcia sylvatica (G.Mey.) DC. em juvenis de Tambaqui (Colossoma macropomum) - VALENTE, Andria Simone Oliveira (Universidade Federal do Oeste do Pará, 2021)
Acute toxicity and anesthetic potential of hydrolate of Myrcia sylvatica (G. Mey.) DC. in juvenile of tambaqui (Colossoma macropomum): Natural products are being tested as anesthetics in fish, in order to mitigate the effects of stress caused by management techniques applied in aquaculture. The objective of this work was to evaluate the use of Myrcia sylvatica hydrolate (MSH) as anesthetic in tambaqui juveniles (Colossoma macropomum), well as assess the lethal concentration (LC50-96h). The concentrations of MSH used to anesthesia experiments, were 15, 20, 25, 30 and 35% (15 fish per treatment). The lethal concentration tested were used 5, 7.5, 10, 12.5 and 15% of MSH concentrations. The physical-chemical variables (temperature, pH, electric conductivity and dissolved oxygen), flow of Na +, K +, Cl-, ammonia and alkalinity of the solutions were evaluated before and after test. The gill mucous cell density (MCD) was determined after 96 hours of exposure to HMS. The 30% concentration of MSH had the best anesthetic induction and recovery times and was indicated for fast handling (about 3min). The acute toxicity test estimated CL50 in 11,19% of MSH. Juveniles of tambaquis exposed to MSH for 96 hours presented high excretion of ammonia and efflux of ions, increasesed with concentration of hydrolate increases. The MCD decresed with increase the concentration of MSH. Thus, the concentration tested of HMS are not indicated for prolonged managements was suggested, because induced osmoregulatory stress.